Arabs Perception of Japanese and English Products Logos - Eibo, Ahmad; Yamashita, Toshiyuki; Kasamatsu, Keiko (Journal of natural sciences, life and applied sciences, 2017)
As a result of increased globalization, the Japanese public and corporations alike are beginning to interact more openly with Arab marketplace. This paper primary focus is to compare products logo images of Japanese characters logotypes to those of English alphabetic logotypes design in the Arab world. By Factor analysis we were able to extract three main images-- “Reliable and Luxurious,” “Creative and Innovative,” and “Familiar and Favorable-- and to reveal by cluster analysis that Japanese characters logotypes products seem to possess the image of highly reliability and creativity than English alphabetic logotypes products. Conceptually, it suggests that although Japanese language is not familiar in the Arab world, products with Japanese character logos design seem to be highly reliable to Arab consumers, and therefore, the familiarization of Japanese language to Arab consumers is not significant for marketing Japanese logotypes products in Arab marketplace, however such as marketing promotion work can be significant to familiarize Arab people with Japanese language.
Keywords: Arab Consumer; Cluster analyses; Logo design; Japan; US